Hydro Democracy: Water Power and Political Power in Ontario - Macfarlane, Daniel; Watson, Andrew (Scientia Canadensis, 2018)
Drawing on Timothy Mitchell’s Carbon Democracy, and using envirotechnical analysis, we probe how the materiality of energy—public hydropower—influenced democracy and governance in Ontario during the early twentieth century. Within Canada, hydro-electricity disproportionately shaped the politics of Ontario and Canada-US relations during the first half of the century. Within the province, it provided the energy-based affluence that underpinned claims for a liberal and democratic society. But residents experienced the consequences of hydropower unevenly. Urban and industrial residents enjoyed most of the benefits, while rural residents and Indigenous peoples living close to hydro developments endured the burdens of development.